Lexicalisation Patterns of Rendering Path Descriptions in Polish Translation from English - Chłopek, Dorota (Slavia Centralis, 2020)
The article pertains to the powerful bi-categorial typology of languages developed by Talmy. The researcher generally points at satellite-framed languages and verb-framed languages in terms of conflating the semantic component of path, either to a satellite placed near a manner verb or to a verb root. Slobin expanded that typology by introducing a class of equipollently framed languages. English and Polish are both satellite-framed languages. Nonetheless, while English colloquially expresses ideas with constructions lexicalising precise path through satellites, Polish translation renders the path, neutralises it, changes it, or omits the path conveyed by the original version, which is illustrated by this paper.
Keywords: Talmy; typology; translation; pattern; English; Polish